(untitled) (American International Journal of Sciences and Engineering Research, 2022)
Die casting has revolutionized manufacturing technology by facilitating mass production while maintaining dimensional accuracy, stability, and strength. It has a broad array of applications in the automotive, lighting, industrial, and domestic sectors. The design parameters have a substantial impact on the quality of die castings. As a response, the aim of this research is set to look into the design characteristics of a hot chamber die-casting. The analysis was carried out using a hot chamber injection molding machine and ZAMAK 5 (Zinc: 96%, Al: 3.5%, and Cu: 0.5%) as the material. To determine the optimal quality parameters for a hot chamber die casting method, the injection speed, chilled water temperature, and cooling time were varied. The injection speeds were set to 4 ms-1, 5 ms-1, and 5 ms-1, respectively, while the chiller temperatures were set at 13°C, and 18°C. In addition, cooling times of 0.8s, 1.2s, 1.6s, and 2s were also recorded. The production analysis was further investigated for casting weights of 40g, 60g, 80g, and 100g. The cooling time was set to 2 seconds, 1.6 seconds, 1.2 seconds, and 0.8 seconds. Following the collection of data, we discovered and examined the most successful and cost-effective parameters for mass production, which offer promises for the industries. JEL Classification Codes: L67, O32, O33.